2017
DOI: 10.21608/bnni.2017.4230
|View full text |Cite
|
Sign up to set email alerts
|

Biological effect of Parsley and honey on side effects of Cisplatin induced nephrotoxicity in experimental male rats

Abstract: ABSTRACThe research was carried out on 50 adult albino male rats (Sprague -Dawley strain) weighing 160±7 g. 10 rats served as control negative group and 40 rats were injected with Cisplatin (7.5 mg/kg bwt, ip)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Despite its beneficial application as an anti-neoplastic agent, CIS causes several toxicities that limit its clinical use including nephrotoxicity, hepatotoxicity, cardiotoxicity, neurotoxicity, and ototoxicity ( Hassan et al, 2020 , Yadav, 2019 , Neamatallah et al, 2018 ). Many experimental studies documented the common toxic side effects associated with CIS, especially nephrotoxicity ( Tahoon, 2017 ). Besides, hepatotoxicity has been identified as a significant dose-limiting side effect of CIS-based chemotherapy ( Apaydin et al, 2018 , Omar et al, 2016a , İşeri et al, 2007 ;) whereas CIS accumulates in the liver at a significant amount secondly to kidney ( Liao et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its beneficial application as an anti-neoplastic agent, CIS causes several toxicities that limit its clinical use including nephrotoxicity, hepatotoxicity, cardiotoxicity, neurotoxicity, and ototoxicity ( Hassan et al, 2020 , Yadav, 2019 , Neamatallah et al, 2018 ). Many experimental studies documented the common toxic side effects associated with CIS, especially nephrotoxicity ( Tahoon, 2017 ). Besides, hepatotoxicity has been identified as a significant dose-limiting side effect of CIS-based chemotherapy ( Apaydin et al, 2018 , Omar et al, 2016a , İşeri et al, 2007 ;) whereas CIS accumulates in the liver at a significant amount secondly to kidney ( Liao et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…CP induces many toxicities, including nephrotoxicity, hepatotoxicity, cardiotoxicity, neurotoxicity and ototoxicity, which restrict its clinical usage [ 2 , 3 , 4 ]. A large number of experimental research papers have provided evidence of the prevalent toxic side effects associated with CP, most notably nephrotoxicity [ 5 ]. Additionally, it has been shown that hepatotoxicity is a prominent dose-limiting adverse effect of CP-based chemotherapy [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%